Social Perception of the Tourist Use of the El Angolo Hunting Preserve: Future of Alternative Tourism - Cornejo, Joyce Mamani; Poma, Delfina Goya Cornejo; Franco, Juan Daniel Martinez; Epiquén, Abdías Chávez; Sifuentes, Lucia Guadalupe Panta; Maquera-Luque, Pedro Jesús; Apaza-Panca, Cynthia Milagros (Journal of Posthumanism, 2025)
Objective: The main objective is to analyze the factors that influence the social perception of the residents of Coto de Caza El Angolo regarding the tourist use of the Protected Natural Area, in order to evaluate its potential for the development of alternative tourism. Theoretical reference: The social perception of residents plays a crucial role in managing the ecological, social and economic impacts of tourism. This perception contributes to the conservation and promotion of tourist attractions, as well as to the promotion of sustainable development. Thus, the interaction of the host population with the tourist environment becomes a key factor for the success of tourism development strategies. Method: The research is of a basic type, with a non-experimental, transversal and exploratory design. A sample of 34 residents was used, to whom a questionnaire composed of 17 items was applied to measure the variable “tourism use” and an observation form for “alternative tourism”. Results and conclusion: The factors “Protection of the ANP CCEA” and “Benefits of tourism” were found to have a positive influence on perception, with “Benefits of tourism” being the factor with the most significant influence. Research implications: The El Angolo Hunting Reserve has significant potential for the development of alternative tourism, particularly in the forms of ecotourism, rural community tourism and adventure tourism, which could contribute to the sustainability of the region. Originality/Value: The study contributes new knowledge to the literature on the development of alternative tourism, focusing its analysis on the social perception of the tourist use of the Coto de Caza El Angolo Protected Natural Area.